Implementing the Hague Convention on the civil aspects of international child abduction: domestic violence, the purpose of the contract and child’s best interests in this content - Vural, Osman (Riga Graduate School of Law, 2019)
In family law cases; custody, guardianship, personal relationship facility, alimony allocation, such as the various needs are subject to litigation. At the same time, the need to protect against domestic violence, neglect or abuse becomes the subject of litigation in this field. In family courts, children often become parties to the claimant or one of the respondent parties. While it is not known exactly how much violence occurs before children's eyes, children are considered invisible victims of this process. As a defense mechanism tool to prevent harmful effect of return of the child, the 1980 Hague Convention on Child Abduction adopts Article 13(b). However there are number of incidents and court decisions that in disputable place where it concluded with the return of the child even there is a violence towards the kid in his/her habitual place of residence. In this study, the author aim to answer the questions “How the Hague Convention on the Civil Aspects of International Child Abduction applies “grave risk of harm”?” and Is fleeing family violence to another country and taking your child considered an abduction?
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Children rights